The Criticism of Roger Mervyn Savory’sApproaches to Safavid History - Ali Salarishadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
As long as the researchers of the Safavid history are concerned, the name of Roger Mervyn Savory is a historian whose name is well known and familiar to all. He is a author whose name has repeatedly been a led in the majority of works full of replicas in the Safavid history. His career has led Safavids studies, especially in Iran, under his control, and the Iranian and Orientalism researchers in this field repeatedly cite him. In the minds of some researchers, Savory is known as a powerful researcher and distinguished Safavidologist, and he has even become himself a reference point for the Safavid history. He has also been introduced by such frequent and repeated writings about himself. However, his accurate and impartial examination of his writings does not prove it. His most important writings are based on the book of the history of the Alamara-i Abbasimi, which was complemented by other researchers of contemporaries. His information and views on the history of the Safavids are one-sided, influenced by the official Safavid sources, and are supposedly exaggerated. This article aims to prove some sources of Savory's insight in a documented way that his writings are non-investigative. He has more to transcribe the sources of Safavid history.